Taller de Mustia Hilachosa (Thanatephorus cucumeris) (2, 1986, San José, Costa Rica). Conferencias (International Center for Tropical Agriculture, 1987)
The 11 conferences given at the 2nd Web Blight (Thanatephorus cucumeris) workshop held in San Jose, Costa Rica, in Nov. 3-7, 1986, as part of CIAT`s Bean Regional Project for Central America and the Caribbean, are presented. Research progress in bean breeding for resistance to T. cucumeris and disease control in Costa Rica, Guatemala, the Dominican Republic, El Salvador, and Panama are presented. Recommendations for various disease testing procedures are given; the International Web Blight Nursery, control strategies, and research goals are also discussed. (CIAT)